A comparison of Sentinel-3-OLCI and Sentinel-2-MSI-derived Chlorophyll-a maps for two large Italian lakes. Issue 10 (3rd October 2019) - Cazzaniga, Ilaria; Bresciani, Mariano; Colombo, Roberto; Della Bella, Valentina; Padula, Rosalba; Giardino, Claudia
ABSTRACT: The twin satellites Sentinel-3 (S3A/B) with Ocean and Land Colour Imager (OLCI) sensors, with a spatial resolution of 300 m, and a revisiting time of 1–2 days, and the twin satellites Sentinel-2 (S2A/B) with MultiSpectral Instrument (MSI) instrument, with a spatial resolution up to 10 m, offer a special opportunity to monitor at both small and large scale, phytoplankton phenology and variation at small time (OLCI) and at small spatial scale (MSI). The aim of this study was to contribute to further testing on MSI imagery, for retrieving chlorophyll- a (chl- a ) concentration, proxy of phytoplankton abundance, in inland waters. Since OLCI has higher revisiting frequency and multiple matchups with MSI, it was also examined as a surrogate for MSI. A common image-processing scheme for both sensors was applied in the two large Italian lakes Garda (oligo-mesotrophic) and Trasimeno (eutrophic). Results showed good performances, both in retrieving atmospherically corrected Remote Sensing Reflectance, and, from this last derived, chl- a concentration maps. Very good accordance was assessed between simultaneous OLCI and MSI derived chl- a maps, both in terms of magnitude, and spatial distribution, despite the fact variations in concentration at small scale were better retrieved by MSI imagery.